Alpha-Methyldopa-Induced Autoimmune Hemolytic Anemia in the Third Trimester of Pregnancy - Charalampos Grigoriadis; Aliki Tympa; Angelos Liapis; Dimitrios Hassiakos; Panagiotis Bakas (Case Reports in Obstetrics and Gynecology)
Alpha-methyldopa has been demonstrated to be safe for use during pregnancy and is now used to treat gestational hypertension. In pregnancy, alpha-methyldopa-induced autoimmune hemolytic anemia does not have typical features and the severity of symptoms ranges from mild fatigue to dyspnea, respiratory failure, and death if left untreated. A case of alpha-methyldopa-induced autoimmune hemolytic anemia in a 36-year-old gravida 2, para 1 woman at 37+6 weeks of gestation is reported herein along with the differential diagnostic procedure and the potential risks to the mother and the fetus.